Developing the Quality of Islamic Colleges in accordance Educational Standards through the National Accreditation System - Arif, Moh.; Fahrudin, Ahmad; Nadaraining, Hasbulloh (Al-Hayat: Journal of Islamic Education, 2025)
Fulfilment of educational quality standards in Islamic religious higher education is essential for maintaining both academic and non-academic excellence. To date, quality assurance has primarily focused on national standards and accreditation in specific scientific fields. However, with the advancement of the tridharma of higher education, quality fulfilment must be assessed against national frameworks and disciplinary standards established by the National Accreditation Board for Higher Education (BAN-PT) and independent accreditation agencies (LAM). This study aims to formulate quality standards grounded in national regulations and accreditation requirements issued by BAN-PT and LAM to strengthen the quality of Islamic religious higher education. This research employs a qualitative phenomenological field design, with data collected through interviews, observations, and documentation. Data validity was ensured through source and time triangulation. The findings reveal that the State Islamic University of Sayyid Ali Rahmatullah Tulungagung, the State Islamic University of Syekh Wasil Kediri, and Hasyim As'ari University Tebuireng Jombang have implemented systematic strategies to ensure the quality of the tridharma, teaching, research, and community service, in accordance with both national and disciplinary accreditation standards. All three institutions integrate Islamic and pesantren-based values into their academic systems. The accreditation results demonstrate the achievement of these quality standards: UIN Sayyid Ali Rahmatullah Tulungagung (51 study programs: 27 Excellent, 19 Very Good, 5 Good), UIN Syekh Wasil Kediri (34 study programs: 10 Excellent, 13 Very Good, 11 Good), and UNHASY Jombang (28 study programs: 6 Excellent, 7 Very Good, 15 Good). The study's original contribution confirms that the development of quality standards in Islamic higher education is not solely oriented toward academic performance, but also integrates Islamic values, morality, and spirituality as defining characteristics of Islamic religious higher education.